Lactobacillus crispatus BC1 Biosurfactant Delivered by Hyalurosomes: An Advanced Strategy to Counteract Candida Biofilm - Angela Abruzzo; Barbara Giordani; Carola Parolin; Priscilla R. De Gregorio; Claudio Foschi; Teresa Cerchiara; Federica Bigucci; Beatrice Vitali; Barbara Luppi (Antibiotics, 2021)
The emergence of resistance to antifungal drugs has made the treatment of vulvovaginal candidiasis (VVC) very challenging. Among natural substances, biosurfactants (BS) produced by Lactobacillus have gained increasing interest in counteracting Candida infections for their proven anti-adhesive properties and safety profile. In the present study, liposomes (LP-BS) or liposomes coated with hyaluronic acid (HY-LP-BS) were prepared in the presence of the BS isolated from the vaginal strain Lactobacillus crispatus BC1 and characterized in terms of size, ζ potential, stability and mucoadhesion. The anti-biofilm activity of free BS, LP-BS and HY-LP-BS was investigated against different Candida albicans and non-albicans strains (C. glabrata, C. lusitaniae, C. tropicalis, C. krusei and C. parapsilosis), clinically isolated from patients affected by VVC. The inhibition of biofilm formation and the dispersal of pre-formed biofilm were evaluated. The obtained phospholipid vesicles showed suitable size for vaginal application and good stability over the storage period. HY-LP-BS exhibited good mucoadhesive properties and the best anti-biofilm profile, both in preventing or limiting the surface colonization by a broad spectrum of Candida species. In conclusion, the formulation of a novel antifungal agent derived from the vaginal microbiota into mucoadhesive nanocarriers appears to be a promising biotherapeutic strategy to counteract vulvovaginal candidiasis.